James J. Dinsmore letter to Thomas H. Kent regarding winter bird sightings, March 1, 1984 - Dinsmore, James J.et al (1984)
James J. Dinsmore letter to Thomas H. Kent was regarding winter bird sightings, March 1, 1984. Most were in central Iowa, and a second sheet recorded bird sightings of his Iowa State University ornithology class. Two species were noted as having documentation: a Northern Goshawk near Lake Rathbun and a Peregrine Falcon in Ames. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of winter 1983-1984. Epson - sheet feed